(Ru(Âµ-Cl)(n6-C6H6)(TFFMS))2(Cl)2: Síntesis, caracterización y evaluación catalítica en la hidrogenación bifásica de olefinas. - Baricelli, Pablo; Castillo, Dayana; Meleán, Luis; Rodríguez, Mariandry; Rosales, Merlin (Ciencia, 1970)
Ver resumen pdf.